PLAFOKON: a new concept for a patient-individual and intervention-specific flexible surgical platform - Bernhard, Lukas; Krumpholz, Roman; Krieger, Yannick; Czempiel, Tobias; Meining, Alexander; Navab, Nassir; Luth, Tim; Wilhelm, Dirk (Surgical Endoscopy, 2022)
Background: Research in the field of surgery is mainly driven by aiming for trauma reduction as well as for personalized treatment concepts. Beyond laparoscopy, other proposed approaches for further reduction of the therapeutic trauma have failed to achieve clinical translation, with few notable exceptions. We believe that this is mainly due to a lack of flexibility and high associated costs. We aimed at addressing these issues by developing a novel minimally invasive operating platform and a preoperative design workflow for patient-individual adaptation and cost-effective rapid manufacturing of surgical manipulators. In this article, we report on the first in-vitro cholecystectomy performed with our operating platform. Methods: The single-port overtube (SPOT) is a snake-like surgical manipulator for minimally invasive interventions. The system layout is highly flexible and can be adapted in design and dimensions for different kinds of surgery, based on patient- and disease-specific parameters. For collecting and analyzing this data, we developed a graphical user interface, which assists clinicians during the preoperative planning phase. Other major components of our operating platform include an instrument management system and a non-sterile user interface. For the trial surgery, we used a validated phantom which was further equipped with a porcine liver including the gallbladder. Results: Following our envisioned preoperative design workflow, a suitable geometry of the surgical manipulator was determined for our trial surgery and rapidly manufactured by means of 3D printing. With this setup, we successfully performed a first in-vitro cholecystectomy, which was completed in 78 min. Conclusions: By conducting the trial surgery, we demonstrated the effectiveness of our PLAFOKON operating platform. While some aspects – especially regarding usability and ergonomics – can be further optimized, the overall performance of the system is highly promising, with sufficient flexibility and strength for conducting the necessary tissue manipulations.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D printing; Individualized surgery; Operating platform; Preoperative planning; Surgical manipulator